KETERBUKAAN INFORMASI MENCEGAH BUDAYA KKN - Astapa, I Gede Agus (Dwijendra University, 2015)
Public (KIP), motivated the desire to create good governance, after the fall of PresidentSoeharto era Era 1998 closure of public information into one of the cultural flourishing of theKKK (Corruption, Collusion and Nepotism) in the days before the 1998 Top condition ,appeared insistence of a number of NGOs (Non Governmental Organization) to make KIP Act.In the end, the Act No. 14 of 2008 passed the House and enacted in 2010.The purpose of this Freedom of Information Law is pushing for a more transparent publicinstitutions and on the other hand the public participation opportunities to facilitate accesspublic information. One of the indicators of the implementation of the Freedom of InformationLaw is the formation of PPID (Information and Documentation Officer) in each public agency.While information for dispute resolution, in accordance Information Freedom of InformationLaw Commission formed, in each province. Information Commission is entitled to take adecision through non-litigation mediation and adjudication, the applicant disputes theinformation requested to the Public Agency.Keywords: public information, dispute information and Information Commission.